Determinants of Executive Directors’ Remuneration in Malaysia’s ACE Market - Hong, Chee Yoong (2016)
This purpose of this study is to analyse and evaluate the determinants of executive directors' remuneration of public listed companies in Malaysia's ACE Market. This study is using panel data analysis on 76 public listed companies in ACE Market from 2009 to 2013 (5 years) with the total of 380 observations. Similar to AIM Market in UK, ACE Market is set up to facilitate emerging companies, which are important to Malaysia economic growth, to raise capital easily. Unfortunately, these companies are shunned by investors because being perceived of having high agency cost and risky. Therefore by studying the executive remuneration, this study would provide an insight for company to design an optimal remuneration packages to align executive directors to shareholders’ interest which in return increasing shareholders’ confidence, interest and investment in this market. The outcome of the study indicates that overall the executive directors' remunerations are fairly aligned to shareholders’ interest. Remuneration is positively determined by company performance and company size which indicates good corporate governance. Interestingly, average remuneration is negatively determined by proportion of executive directors to the board which show ACE companies have set limited budget for hiring executive directors. Unfortunately, executive directors with high share ownership have strong influence on the remuneration which indicates boards of directors have failed to suppress executive directors’ influence. The implication of this study shows that it is important for government to impose some regulations to reduce the influence of executive directors on the board. One of the options available is to compel companies to have shareholders voting on executive directors’ remuneration which encourage boards to justify the remuneration packages to shareholders. Another option is to make it compulsory for remuneration board to consist of non-executive directors only in order have impartial decision on the remuneration packages.